2016
DOI: 10.1016/j.echu.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Chiropractic Identity in the United States: Wisdom, Courage, and Strength

Abstract: ObjectiveThe objective of this paper was to discuss the chiropractic profession’s identity and 3 contentious issues related to identity.DiscussionThe various clinical specialties and independent groups in the chiropractic profession are so different in their beliefs, practice styles, and political agendas that a common identity is unlikely to be created. Areas of disagreement, including advanced practice, vertebral subluxation, and the philosophy of chiropractic, continue to separate those in the profession. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Some chiropractors are certified in internal medicine, diagnostic imaging, or a variety of other areas. 20 As a result, it is possible that only those chiropractors that have a particular identity or practice style may be approached by patients to discuss DTC genomics results. This study found that graduates of the university also have a variety of practice styles consistent with what is known throughout the profession.…”
Section: Discussionmentioning
confidence: 99%
“…Some chiropractors are certified in internal medicine, diagnostic imaging, or a variety of other areas. 20 As a result, it is possible that only those chiropractors that have a particular identity or practice style may be approached by patients to discuss DTC genomics results. This study found that graduates of the university also have a variety of practice styles consistent with what is known throughout the profession.…”
Section: Discussionmentioning
confidence: 99%
“…To date, neither side has been able to find true common ground [ 1 , 6 ], often using arguments and tactics that have increased division, further split the profession and negatively affected social standing [ 50 ].…”
Section: A Mixed Blessingmentioning
confidence: 99%
“…Internally, the divergences have manifested themselves as an identity struggle, with many chiropractors seeking a moderate, evidence based position while others strive to retain vitalistic ideas [ 1 , 2 ]. The disparity between these groups has divided the profession and invited ridicule from the both the scientific community [ 3 ] and the public at large [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, this journal published a series of commentaries on the topic of chiropractic identity and opinions ranged from the idea of focusing on correction or management of subluxation in the more historical sense [9] to advanced clinical practice and spine care as a specialty for the profession [10,11]. Interestingly, one author summed it up in that, "For any statement of professional identity to be effective, it requires widespread adoption by the profession" [11].…”
Section: Introductionmentioning
confidence: 99%